Avaliação dos efeitos do tratamento com o fator estimulador de colônias de granulócitos (G-CSF) na cardiopatia chagásica crônica experimental - Vasconcelos, Juliana Fraga (2012)
Chronic Chagasic cardiomyopathy (CChC) affects approximately 30% of individuals infected with Trypanosoma cruzi, and results from a progressive destruction of the myocardium, causing the development of heart failure and death of the patients. The lack of therapeutic alternatives and the socio-economic impact of the CChC emphasize the importance of developing new treatments for this disease. The G-CSF, a cytokine already used in clinical practice, has been studied for its therapeutic potential in other experimental models of cardiac diseases. In this study we evaluated the therapeutic effects of G-CSF in a model CChC. After approval by the local ethics committee, C57BL/6 mice infected with T. cruzi for six months were treated with G-CSF in 3 courses (200 µg / kg / day for 5 days) with an interval between the cycles of one week. Infected animals had severe conduction disturbances, partially reversed by the use of G-CSF. In addition, an improvement of the cardiorespiratory function was observed, as assessed by spirometry. We observed a reduction of the inflammatory infiltrate associated with reduced production of SDF-1, ICAM-1 and syndecam-4 and increasing apoptosis of leukocytes in the hearts of the animals treated with G-CSF. We also found that both macrophages, as well as the production of galectin-3, were reduced in the group G-CSF, which is associated with the decrease of fibrosis in the group. Treatment with G-CSF modulates the production of IFN-γ and TNFα, reduced the gene expression of Tbet, while providing a slight reduction in IL-17 without any significant changes in IL-4 or GATA-3. Treatment with G-CSF induced the migration of Treg cells from the bone marrow to the periphery, as demonstrated by increasing this population in spleen and heart of the treated animals. The presence of IL-10-producing Foxp3+ cells, as well as an increased production of IL-10 on heart and spleen, suggests that this cytokine contributes to the modulation of the inflammatory response. Despite the reduction of the inflammatory response, we also observed a reduction in parasitic load in the hearts of the animals treated with G-CSF. The activity of G-CSF on the parasite was confirmed in experiments in vitro, in which we found a reduction in the viability of trypomastigotes and in the number of infected macrophages and amastigotes/macrophage. In conclusion, G-CSF exerts multiple effects in mice infected with T. cruzi, acting as a modulatory agent in the immune response and promoting the reduction of parasite load, allowing the improvement of cardiac function in chronic Chagas disease model, results which encourage the study of its therapeutic potential in patients with Chagas disease.